Improving nutrients availability in peat soil using EFB compost and Effective Microororganism (EM) / Muhammad Nizam Supian - Supian, Muhammad Nizam (Faculty of Plantation and Agrotechnology, 2018)
This study intends to determine the amount of released nutrients and to examine the highest nutrient release in peat soils through the application of different rate of Empty Fruits Bunch (EFB) and Effective Microorganisms (EM). The improvement of nutrient released in the soil is compared to the standard practice applied in the oil palm plantation. In this study, peat soil samples were filled into polybags and 5 different rates of EFB and EM, respectively, were applied. Soil sampling was conducted in 2 weeks intervals for 8 weeks. Samples were analyzed for soil pH, exchangeable K, Ca, Mg and Na, available P, iron and aluminum. Result showed that there is a significance effects of EFB and EM application on soil pH, concentration of Ca, Al and Fe. Compared to the standard practice T3 (Peat: 1kg + EFB: 20g), it is suggested that the application of T5 (Peat: 600g + EFB: 12g) could improve the amount of nutrient release in peat soils.